Hyponatremia After Intracranial Hemorrhage: Cerebral Salt Wasting Syndrome (CSWS) or The Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH)? - Wan Novriza Wijaya; Novita Anggraeni; Sony; Andrea Valentino (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Hyponatremia is a common electrolyte disorder encountered in neurosurgical patients, often associated with significant morbidity and mortality. This case report highlights the importance of recognizing and appropriately managing cerebral salt wasting syndrome (CSWS), a rare but important cause of hyponatremia in neurosurgical patients, often following intracranial hemorrhage (ICH). Distinguishing CSWS from the syndrome of inappropriate antidiuretic hormone secretion (SIADH) is crucial for appropriate management. Case presentation: A 56-year-old male with a history of hypertension and diabetes mellitus presented with sudden-onset left-sided weakness and decreased consciousness following an ICH. He underwent a ventriculoperitoneal (VP) shunt placement for hydrocephalus. Post-operatively, he developed hyponatremia with elevated urine sodium levels and hypovolemia, suggestive of CSWS. The patient was treated with fluid replacement therapy, including hypertonic saline, and desmopressin, resulting in improvement in his hyponatremia. Conclusion: CSWS is an important cause of hyponatremia in neurosurgical patients. Prompt diagnosis and appropriate management, including fluid replacement and potentially desmopressin, can improve patient outcomes. This case underscores the need for a high index of suspicion for CSWS in neurosurgical patients presenting with hyponatremia and highlights the importance of careful monitoring and individualized treatment strategies.